Development of a vacuum cleaner mobile robot - Sardağ, Alp. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1998., 1998)
This study presents the results of the development of an autonomous mobile robot which is a domestic autonomous vacuum cleaner. The robot is designed according to some new concepts established in this field during the last decade. These principles are artificial life, subsumption architecture and other bottom-up methodologies. These ideas have been applied to the complete robot design, spanning from the shape of the robot to the sensors, from the electronics to the software control structure. We have built the robot and programmed it to perform various reactive behaviours. The autonomous vacuum cleaner performs area coverage in a room by combining distinct behaviors. The robot has 11 sensors which are used in the algorithms examined. The robot behaviors allow it to avoid obstacles, follow walls, break out of confined areas, detect floor and find a docking area. The performance tests are done through a dedicated simulator and by observation. The experiments performed here were both in the simulator and real-time it appears that the best area coverage algorithm among those tried consisted of a random walk with a probability of 0.10 for following a wall after each encounter with an obstacle.
Keywords: Mobile robots.; Autonomous robots.; Vacuum cleaners.